Comprehensive analysis of air waves and their impact on the value of solar radiation in Iraq (Journal of the College of Basic Education, 2022)
The climate of Iraq is the outcome of the interaction of several complex factors, including the astronomical and geographical location, its location in relation to the water bodies and the characteristics of the air masses affecting it throughout the year and its variation from one place to another. Barometric winds moving from west to east have a major role in shaping the pressure systems located below, and thus affecting the actual brightness rates, which witnessed a clear discrepancy between the stations of the study area. We note that the highest rates of brightness were recorded in the southern and western stations and the lowest in the northwestern stations, and this This is due to the presence of air waves represented by dents at high rates in the southern and western stations, while the northwestern stations recorded a rise in the number of grooves, which reduces the actual brightness rates.